Return on investment on facebook adds: Quantitative research - Nina Angelovska (UTMS Journal of Economics, 2022)
Facebook ads are widely used by companies around the world who spend significant budget on this promotional tool. We focus in this research on financial returns of Facebook ads designed towards reaching sales (conversions), particularly short-term profitability. The aim of this research is to give answers to the questions of interest to mangers and academics: how profitable is Facebook advertisement for businesses and what factors affects profitability. To achieve the goal we analyse data of 258 Facebook ad campaigns on monthly bases, made by the group-buying site Grouper. Firstly, we measure return on investment on Facebook ads (ROFI) as indicator for short-term profitability. The results show that one Euro investment in Facebook ads will return eight Euro on average. Secondly, to explore what factors affects ROFI we perform regression analysis and results show 'cost per conversion' to be a significant factor affecting ROFI or a decrease of 1 percentage in cost per conversion will increase ROFI for 12 points.
Keywords: M27; M37; 330; e-commerce; promotion; digital advertising; group buying site; ROFI; North Macedonia